The Impact of Islamic Banks on Financial Soundness Indicators - Almayatah, Suleiman Abid A. (International Review of Management and Marketing, 2018)
This study aims to determine the impact of Islamic banks on the financial soundness Indicators, considering that these indicators are mirror that reflect the ability of the banking system in absorbing crises and efficiently investing in the operation of the money. This study uses the capital adequacy index as a measurement on indicators of total financial soundness, where the dependent variable is (percentage of Islamic banks, total banks credit, total capital of the banking sector). The study included countries where Islamic banking represents high percentage of total banks, where these countries should publish the relevant data. The study sample represents nine countries around the world. The pool data model used to estimate the impact of Islamic banking, where the methodology used enhanced by using (the pooled time series-cross section analysis) to improve measurement efficiency. The results of the study shows positive impact ratio of Islamic banking on financial soundness indicators represented by the ratio of capital adequacy and the results show that the increase in the percentage of Islamic banking by 1% has the effect of increasing the proportion of capital adequacy by 0.21%. Keywords: Financial Soundness Indicators, Islamic Banks, Capital Adequacy Ratio, Basel Standards JEL Classifications: E22.G01.G21